ANALISIS TINGKAT PEMAHAMAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SUMATERA UTARA MENGENAI PASAR MODAL DI INDONESIA - Elfrida Lasmauhur Purba; Coki Ahmad Syahwier (Ekonomi dan Keuangan, 2014)
This research aims to know the understanding of students in Faculty of Economics University of Sumatera Utara about The Stock Market in Indonesia.This research used method of Descriptive Analysis, Manova Test, and Kruskal-Wallis Test. The quality of its data is tested by Validity Test and Reliability Test.In collecting the data, this research is conducted by interview and questionnaireto the six major in Faculty of Economics in USU with 97 samples. After the data had been collected, the data was analyzed and interpreted until a conclussion is found.From the result of the resarch, it’s concluded that more than half of the students in Faculty of Economics USU understand about The Stock Market in Indonesia. The students with the highest level of understanding is Accounting, followed by Management, Economics, Accounting (D3). The second lowest is Monetary (D3). While the students with the lowest understanding is Secretary (D3).Keywords: Stock Market, Understanding, Economics Student